2011
DOI: 10.1111/j.1526-4610.2011.01962.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache in Systemic Lupus Erythematosus vs Multiple Sclerosis: A Prospective Comparative Study

Abstract: Migraine should be no longer considered a neurologic manifestation of systemic or organ-specific autoimmunity. Increased migraine prevalence in these patients found in previous studies could be due to methodological weaknesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 33 publications
4
51
1
1
Order By: Relevance
“…In some case-control studies, a higher frequency of migraine without aura is found in patients with SLE [15], antiphospholipid antibody syndrome [16], and Sjogren syndrome [17] than in controls. In SLE [18] and Sjogren syndrome patients [17], the frequency of chronic tension headache is higher than controls also. Recently, a variety of autoimmune disorders have been disclosed in 61% of stabbing headache patients [19].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In some case-control studies, a higher frequency of migraine without aura is found in patients with SLE [15], antiphospholipid antibody syndrome [16], and Sjogren syndrome [17] than in controls. In SLE [18] and Sjogren syndrome patients [17], the frequency of chronic tension headache is higher than controls also. Recently, a variety of autoimmune disorders have been disclosed in 61% of stabbing headache patients [19].…”
Section: Discussionmentioning
confidence: 95%
“…Autoimmune disorders are currently proposed as provoking primary headache syndromes by an involvement of the trigeminal nucleus or tract through inflammation, demyelination or vasculitic ischemia [15][16][17][18][19][20]. In NH, the painful area is generally located at the parietal area which is innervated by the ophthalmic branch of trigeminal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Another study focusing on the risk of newly diagnosed asthma showed that the relative risk of developing asthma in migraineurs was 1.17 compared with non-migraineurs [2]. Moreover, although the association with irritable bowel disease, endometriosis, celiac disorder and LES has been investigated, further studies are needed to confirm the hypothesis [2,[27][28][29][30][31].…”
Section: Other Comorbid Disordersmentioning
confidence: 95%
“…Later, other researchers began to explore the relationship between these two clinical abnormalities. All studies have confirmed the association between migraine and MS. 2,5,11,13 Some studies such as studies done by Vecca, Katsiari and Nicoletti did not find any significant relationship between MS and migraine with aura. 11,12,14 Conversely, the very researchers found a significant association between MS and the occurrence of migraine without aura.…”
Section: Discussionmentioning
confidence: 99%